Post-emergent herbicides in Oryz Efficacy of post-emergent herbicides on Oryza latifolia Desv. (broadleaf rice) and selectivity to Palmar 18 rice - Picado-Arroyo, Grettel; Herrera-Murillo, Franklin (Agronomía Mesoamericana, 2022)
Introduction. Oryza latifolia Desv. is a problematic weed in rice plantations given the competition it exerts and the limited availability of herbicides for its control, which are selective to conventional rice varieties. Objective. To identify post-emergent herbicides effective against O. latifolia and selective to the Palmar 18 rice (Oryza sativa L.) variety. Materials and methods. From April to November 2019 at the Fabio Baudrit Moreno Agricultural Experimental Station, Alajuela, Costa Rica, two experiments were carried out in pots and under greenhouse conditions; in the first one, the herbicides fenoxaprop-p-ethyl 50, 70, 90 g a.i. ha-1, sethoxydim 125, 225, 325 g a.i. ha-1, and profoxydim 150, 200, 250 g a.i. ha-1, applied on O. latifolia plants with two to three leaves, were evaluated. An unrestricted randomized experimental design with ten treatments (a control without herbicide was included), and five replications was used. In the second experiment, the selectivity of fenoxaprop-p-ethyl 50 g a.i. ha-1, sethoxydim 125 g a.i. ha-1, and profoxydim 150 g a.i. ha-1, was evaluated on the conventional variety Palmar 18 in 2-3 and 4-5 leaves. An unrestricted randomized design was used with a 3x2 factorial arrangement (three herbicides and two stages of development), two controls without herbicides and six replications. Results. All herbicides at the doses evaluated controlled between 96 and 100 % of O. latifolia. The herbicides profoxydim and sethoxydim showed to be selective to Palmar 18 rice, under the conditions in which the research was carried out, but not fenoxaprop, which caused severe damage to Palmar 18 rice plants. Conclusion. Profoxydim 150 g a.i. ha-1 and sethoxydim 125 g a.i. ha-1 were effective against O. latifolia and only caused slight temporary damage to the Palmar 18 rice variety.